Pengaruh Penerapan Sapta Pesona terhadap Kepuasan Pengunjung di Pantai Istana Amal Kabupaten Penajam Paser Utara - Mega Sepriyanti Gede (Jurnal Kajian dan Terapan Pariwisata, 2022)
Sapta Pesona is one of the efforts made to develop the tourism industry. Istana Amal Beach is a new tourist destination in Penajam Paser Utara Regency. Based on the data, it can be seen that there has been an increase and decrease in tourist visits due to the COVID-19 pandemic. This study aims to determine the effect of sapta pesona on visitor satisfaction at Istana Amal Beach.the type of research is associative with a quantitative approach. This data was analysed by simple linier regression and using SPSS version 25. The population in this study were all tourists who had visited Istana Amal Beach. Using the Lemeshow formula with calculation results of 100 respondents and non-probability sampling with purposive sampling method. From the tests conducted, it is known that (1) sapta pesona has a significant effect on visitor satisfaction; and (2) Istana Amal Beach shows the characteristics of applying sapta pesona properly based on the guidebook for tourism awareness groups, that is : increase in tourist arrivals, prospective tourism business, and increase in job opportunities